(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article highlights the numerous benefits of being a polyglot such as enhanced communication skills, cognitive abilities, and cultural understanding, to personal growth and enhanced confidence. Although learning languages can be challenging and difficult to manage, it certainly has so many advantages in every sphere of globalized world. This article illustrates those advantages and encourages becoming a Polyglot.